21st birthday - Patterson, James; Paetro, Maxine (Little, Brown and Company, 2021)
"Detective Lindsay Boxer vows to protect a young woman from a serial killer long enough to see her twenty-first birthday. When Tara Burke goes missing with her baby girl, all eyes are on her husband, Lucas. He paints her not as a missing person but a wayward wife--until a gruesome piece of evidence turns the investigation criminal. ADA Yuki Castellano sizes Lucas up as a textbook domestic offender...who suddenly puts forward an unexpected suspect. If what Lucas tells law enforcement has even a grain of truth, there isn't a woman in the state of California who's safe"
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Women's Murder Club (Imaginary organization) -- Fiction; Women detectives -- California -- San Francisco -- Fiction; Murder -- Investigation -- Fiction; San Francisco (Calif.) -- Fiction